Using passing network measures to determine the performance difference between foreign and domestic outfielder players in Chinese Football Super League - Yu, Q.; Gai, Y.; Gong, B.; Gómez, M. A.; Cui, Y. (International Journal of Sports Science & Coaching, 2020)
The study was aimed to identify the passing performances related to social network between domestic (Chinese) and foreign (non-Chinese) players that contributed to the offensive play according to playing positions in Chinese Football Super League. Data were collected from all 16 teams, with 63,446 passes from 8885 player observations of 346 unique players (258 domestic and 88 foreign) being filtered. Nine network metrics were adopted to assess the passing performance between two player groups. The results revealed that foreign players, especially midfielders and forwards, had increased values than domestic counterparts in passes in, indegree, stress, partner and betweenness centrality (standardised Cohen`s d range: 0.18-0.62; inference: possibly to most likely). Moreover, foreign midfielders also demonstrated higher values in passes out, outdegree and closeness centrality (0.30-0.56; likely to most likely). The analysis of passing performance allows for a better understanding of team`s attacking properties and highlights the prominent role foreign players act within the build of attack. It is possible that recruiting high-level overseas players contribute to Chinese teams` goal scoring performance, but coaching staffs and team managers should take cautions in terms of the degree of reliance on them, as the development of domestic midfielders and forwards would be compromised.